Challenges of school governance: a case study of a secondary school in Gauteng - Mpanza, Gugulethu (My University, 2015)
The main purpose of the study was to investigate the challenges faced by School Governing Bodies (SGBs) regarding school governance in Gauteng Province, South Africa, and specifically a public secondary school in Soweto, west of Johannesburg. A qualitative approach was applied to the case study and data was collected from participants via semi-structured interviews, observational field notes and document analysis. This study began with an overview of the background and purpose for this research together with the primary research and secondary research questions. The literature review focused on the various aspects relating to school governance including an international perspective. South Africa’s non-democratic and current democratic approach to its challenges was explored. The qualitative research methodology findings led to data being classified into three main themes, namely (i) the role of SGB components, (ii) the effectiveness of the SGB, and (iii) the competency of the SGB. These themes within the categories framework were used to discuss the findings. The study then provides an analysis and interpretation of results which informed the conclusion and recommendations of the research. Three critical findings emerge from the study. First is the allocation of the prescribed role and functions within the SASA (1996). Secondly, there is a misunderstanding and misinterpretation of the roles and responsibilities of the SGB members and the legislation. Thirdly, there is a lack of capacity, knowledge and skills by SGB members to efficiently and effectively execute their required functions. Therefore, this study recommends a comparative study of the monitoring tools and techniques used to monitor the effectiveness of the SGB at the selected schools in Soweto.
Thesis (M.M. (Public and Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2015.